Relationship between treatment center case volume and survival for localized Ewing sarcoma: The role of radiotherapy timing. Issue 11 (2nd September 2020) - Lin, Timothy A.; Ludmir, Ethan B.; Liao, Kai‐Ping; McAleer, Mary Frances; Bishop, Andrew J.; Grosshans, David; McGovern, Susan; Woodhouse, Kristina D.; Paulino, Arnold C.; Yeboa, Debra Nana
Abstract: In the treatment of localized Ewing sarcoma (EWS), delays in local therapy are known to adversely impact overall survival (OS). However, the role of treatment center volume in EWS outcomes, and the interaction between center volume and local therapy timing with definitive radiotherapy, remains unknown. Using the National Cancer Database, we demonstrate that treatment at the lowest EWS volume centers is associated with reduced OS, explained partly by higher rates of delayed local therapy. Treatment at the highest volume centers results in improved OS, but appears independent of radiotherapy timing. Future efforts to improve care for EWS patients across treatment centers are imperative.